Systematic Literature Review: Ethnoscience-Based E-Module Development with Project-Based Learning Using Google Site to Enhance Student Creativity in Chemistry - Wahyu Zahraini; Agus Abhi Purwoko; Yunita Arian S. Anwar (Balai Publikasi Indonesia, 2025)
Fostering student creativity is essential to meet the demands of 21st-century learning, which has been integrated into Indonesia’s current national education framework through the implementation of the Independent Curriculum (Kurikulum Merdeka). This study aims to examine research trends related to the development of ethnoscience-integrated e-modules using the Project-Based Learning (PjBL) model in the context of chemistry education to enhance students' creativity. A descriptive-analytical method was employed in this study, with data collected from scientific documents indexed in Google Scholar between 2015 and 2024. The research tools used included Publish or Perish and Dimensions.ai, while data visualization and trend mapping were conducted using VOSviewer. The results indicate a significant decline in publication trends over the past three years, suggesting a decreasing focus on this intersection of digital learning, contextual science, and creativity development. These findings highlight a promising opportunity for future researchers to explore underrepresented themes and keywords identified in this review, particularly those that integrate local wisdom, digital platforms, and creativity enhancement in science education.